Checklist and description of three new chromatic patterns of Pachycoris torridus (Scopoli, 1772) (Hemiptera: Scutelleridae) - Souza-firmino, Tatiani Seni De; Alevi, Kaio Cesar Chaboli; Pereira, Luis Lenin Vicente; Banho, Cecilia Artico; Silva, Fernando Cesar; Souza, Emi Rosane Silistino De; Itoyama, Mary Massumi (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2016)
In the present paper, 27 chromatic patterns of the specie Pachycoris torridus (Scopoli, 1772) were grouped and three new patterns are described. Because of this high phenotypic polymorphism, P. torridus already been registered eight times as a new specie, highlighting the importance of the application of different tools to assist in taxonomy of this hemipterous of economic importance.

No presente artigo, 27 padrões cromáticos da espécie Pachycoris torridus (Scopoli, 1772) são agrupados e três novos padrões são descritos. Devido a esse grande polimorfismo fenotípico, P. torridus já foi registrado oito vezes como espécie nova, o que ressalta a importância da aplicação de diferentes ferramentas para auxiliar na taxonomia desse hemíptero de importância econômica.
Checklist e descrição de três novos padrões cromáticos de Pachycoris torridus (Scopoli, 1772) (Hemiptera: Scutelleridae)
Keywords: Insect; Heteroptera; polymorphism; agricultural pest; Insecta; Heteroptera; polimorfismo; peste agrícola